Learning Mandarin as a third language among non-native speakers by using Alpha M (an educational card game) / Sheau Ping Wee ... [et al.] - Sheau, Ping Wee; Ai, Nyet Chan; Liew, Chin Ying; Yit, Lian Liew (Universiti Teknologi MARA, Kedah, 2023)
Learning Mandarin as a third language (MTL) becomes more challenging as learners progress to a higher level yet they are still expected to be able to recognize, comprehend, write, and pronounce more Chinese characters. The typical traditional drills which are commonly practised often make the lessons dull and subsequently, kill the interest in learners. Hence, there is a need to incorporate engaging activities as a platform for the learners to communicate by using Mandarin and at the same time, apply the knowledge that they have been taught. This gave birth to Alpha M (an educational card game) which comprises 80 Chinese characters and 3 punctuation marks for novice of a MTL course. It is most suitably used as a manipulative for the teaching-and-learning sessions. The main goals of Alpha M are to enhance the learning experience of learners in a few ways, namely Chinese characters recognition and comprehension, Chinese phonetic system (Hànyǔ Pīnyīn) practice, and construction of meaningful phrases, clauses as well as sentences for daily communication. Evaluation on the effectiveness of Alpha M shows learners of MLT had fun and engaging experiences during their learning process. A pre-post test has been conducted to evaluate the effectiveness of the Alpha M. The pre-post tests show significant improvements in the identification of Chinese characters among the samples. Since it has proven to be effective,the subsequent move will be the commercialization of Alpha M.